Multiple Myeloma Presenting with Severe Back Pain: A Case Report - Sopian, Fitri Rahmawati; Suryo, Martin Firman (Syntax Corporation, 2024)
This study aims to highlight the diagnostic challenges and management strategies in a case of Multiple Myeloma (MM), a hematologic malignancy characterized by malignant plasma cells in the bone marrow. The case involves a 40-year-old male who presented with persistent back pain for two months, impacting his mobility. Initial physical and neurological assessments were largely unremarkable, but laboratory and radiological investigations revealed multiple osteolytic lesions suggestive of MM. Typical MM symptoms include hypercalcemia, renal dysfunction, anemia, and bone pain, though this patient did not present all the classical signs, which underscores the diagnostic complexity. A bone marrow puncture was planned for definitive diagnosis. The study emphasizes the importance of radiological evaluation in MM diagnosis and the need for prompt treatment addressing acute symptoms, such as hypercalcemia and renal insufficiency, followed by a comprehensive long-term management plan. Early oncology consultation and a multidisciplinary approach are critical for improving patient outcomes. The case demonstrates the importance of a holistic, symptom-based approach in MM management, incorporating regular monitoring and coordinated care to address the multifaceted nature of the disease.